2020
DOI: 10.22454/primer.2020.861306
|View full text |Cite
|
Sign up to set email alerts
|

Family Medicine Telehealth Clinic With Medical Students

Abstract: COVID-19 has altered clinical clerkships for medical students, providing an opportunity for telehealth with medical students to take center stage in the age of technology. This research brief demonstrates why and how to incorporate medical students into telehealth. For the purposes of clinical students, telehealth is a better educational alternative to in-person patient care than online modules. We performed a successful outpatient family medicine telehealth pilot program at the Medical University of South Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Cain et al [ 19 ] reported family medicine clerkship students reviewing and documenting on EMR charts later reviewed by the attending. Similar pilot programs were reported by family medicine telehealth clinics at the Medical University of South Carolina [ 21 ]. A unique program led by Stanford University’s students, called Cardinal Free Clinics, opened immediately after the onset of the pandemic, and changed to a telehealth clinic model when in-person patient clinics were forced to close due to university COVID-19 policies [ 22 ].…”
Section: Resultsmentioning
confidence: 60%
See 4 more Smart Citations
“…Cain et al [ 19 ] reported family medicine clerkship students reviewing and documenting on EMR charts later reviewed by the attending. Similar pilot programs were reported by family medicine telehealth clinics at the Medical University of South Carolina [ 21 ]. A unique program led by Stanford University’s students, called Cardinal Free Clinics, opened immediately after the onset of the pandemic, and changed to a telehealth clinic model when in-person patient clinics were forced to close due to university COVID-19 policies [ 22 ].…”
Section: Resultsmentioning
confidence: 60%
“…Adding to previous reviews, we found reports using telemedicine to overcome the challenges in clinical education amidst the pandemic disruption ( Table 2 ). 17 papers [ 8 , 9 , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ] described the use of telemedicine as an educational tool mostly for clerkship rotations but three also included pre-clinical year students. Whilst telemedicine was mainly implemented in university hospitals, six programs were also executed in the community.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations